Analyses of simple and intercooled recuperated direct Brayton helium gas turbine cycles for Generation IV reactor power plants - Gad-Briggs, Arnold; Pilidis, Pericles (American Society of Mechanical Engineers (ASME), 2016)
As a nongreenhouse gas-emitting source, the benefits of nuclear as a main power-generation alternative are yet to be fully explored; part of the reason is due to the significant implementation costs. However, with cycle efficiencies of 45–50% in current studies, it can be argued that the long-term benefits outweigh the initial costs, if developed under the Generation-IV (Gen-IV) framework. The main objective of this study is to analyze the effects of pressure and temperature ratios (TRs) including sensitivity analyses of component efficiencies, ambient temperature, component losses and pressure losses on cycle efficiency and specific work. The results obtained indicate that pressure losses and recuperator effectiveness have the greatest impact on cycle efficiency and specific work. The analyses intend to aid development of the simple cycle recuperated (SCR) and intercooled cycle recuperated (ICR) cycles, applicable to gas-cooled fast reactors (GFRs) and very-high-temperature reactors (VHTRs), in which helium is the coolant.
Keywords: Gen-IV; efficiency; specific work; cycle; nuclear power plants; performance; simple; intercooled